LABORATORY DIAGNOSIS AND CLINICAL SIGNS OF CANINE VISCERAL LEISHMANIASIS IN DOGS EXAMINED AT THE CENTER FOR ZOONOSIS CONTROL IN CAMPO GRANDE – MS, BRAZIL - Cunha, Rodrigo Casquero; Andreotti, Renato; Silva, Elaine; Pereira, Elisângela; Sato, Tayra; Thomaz-Soccol, Vanete (Archives of Veterinary Science, 2012)
Visceral leishmaniasis is a type of zoonosis caused by several Leishmania species endemic to tropical, subtropical, and Mediterranean climate regions. Dogs are the primary source of infection in urban areas and can be symptomatic or asymptomatic. This study focused on the observation of clinical signs of leishmaniasis in dogs in Campo Grande, Mato Grosso do Sul, Brazil. Samples from affected animals were analyzed using indirect fluorescent antibody (IFA) tests, an enzyme-linked immunosorbent assay (ELISA), and polymerase chain reaction (PCR) assays to determine the optimal diagnostic tool for use on animals that present clinical symptoms. A predominance of clinical symptoms affecting the integumentary system was observed, and splenomegaly and hepatomegaly were the most important pathological signs. Among the diagnostic tests, the greatest agreement was seen between ELISA and IFA, followed by ELISA and PCR, and finally IFA and PCR. PCR diagnostic results showed the greatest extent of correlation with clinical signs, followed by ELISA and then IFA. When choosing a diagnostic method, veterinarians should consider the clinical signs and health status of the patient.